2002
DOI: 10.4321/s0212-71992002000400005
|View full text |Cite
|
Sign up to set email alerts
|

Trastornos gastrointestinales en Guatemala y su relación con infecciones parasitarias

Abstract: Bibliografía FE DE ERRATAS El trabajo "Trastornos gastrointestinales en Guatemala y su relación con infecciones parasitarias" fue publicado en el nº de Enero de 2002 pags. 3-6. Por un error en la impresión fue publicado anómalamente, apareciendo el texto de sus distintos apartados, mezclado de forma inconexa. La versión que aparece en este número, págs. 179-182, es la original y v á l i d a .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
1
3
0
2
Order By: Relevance
“…Evidence for postinfectious IBS secondary to low-grade inflammation was demonstrated by D'Anchino et. al., [19]. In the present study, G. lamblia cyst was detected in three (1.5%) of IBS patients; this was similar to the results of Grazioli et.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Evidence for postinfectious IBS secondary to low-grade inflammation was demonstrated by D'Anchino et. al., [19]. In the present study, G. lamblia cyst was detected in three (1.5%) of IBS patients; this was similar to the results of Grazioli et.…”
Section: Discussionsupporting
confidence: 81%
“…This result is consistent with Bujanda et. al., who showed that, 49% of the patients with symptoms suggestive of gastrointestinal functional disorders were, or had previously been, diagnosed with parasitic infection [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a study from Venezuela reported an IBS prevalence of 16.8%, with 81.6% of those affected being women and 18.4% men [3]. Studies on indigenous populations in Latin America revealed a high prevalence of IBS, which was similar to that in the rest of the population [4]. • Data from Africa are very scarce.…”
Section: Global Prevalence and Incidencementioning
confidence: 99%
“…Se observa una mayor inclinación por el sexo masculino de presentar trastornos digestivos, aunque se puede deber a la mayor población de hombres que de mujeres que participaron en el estudio; ya que autores mencionan que la prevalencia en los países industrializados tanto de hombre como de mujeres es similar [8]. Con relación a la edad es de destacar que posiblemente se observe la presencia de Helicobacter pylori con una mayor prevalencia en el grupo de pacientes referenciados entre las edades de 30 a 45 años como lo referencian otros autores [9].…”
Section: Díaz Pérez Anderson 10unclassified